Liturgia i teologia chrztu św. Augustyna w Mediolanie - Eckmann, Augustyn (Vox Patrum, 1988)
The liturgy of baptism performed by St. Ambrose consisted of three parts: prebaptismal, baptismal and postbaptismal rites.